Ethyl biodiesel: Microwave irradiation aiding ethanolysis of waste cooking oil. - Barbosa, Sandro L.; Miranda, Savio E. O.; Klein, Stanlei Ivair [UNESP]; Hurtado, Gabriela R.; Baroni, Adriano C. M.; Dabdoub, Miguel J. (My University, 2013)
We describe a methodology to produce biodiesel of excellent quality from waste cooking oil, NaOH catalyst and ethanol, by accelerating the transesterification reaction with microwave irradiation from an unmodified household microwave owen. The resulting Waste Cooking Oil Ethyl Esters were evaluated according to the physical and chemical properties demanded by regulatory standards for biodiesels, and a brief discussion of the meaning and scope of these quality control parameters directly related to biodiesel is also presented. Keywords: Ethylic Biodiesel; Waste Cooking Oil; Microwave Irradiation; Biotechnology; Quality Control; Biofuel.